Interactive Effects of Glucocorticoids and Cytochrome P450 Polymorphisms on the Plasma Trough Concentrations of Voriconazole - Jia, Su-jie; Gao, Ke-qin; Huang, Pan-hao; Guo, Ren; Zuo, Xiao-cong; Xia, Qing; Hu, Shuang-yao; Yu, Zhen; Xie, Yue-liang (Frontiers in Pharmacology, 2021)
Aims: To explore the interactive influence of glucocorticoids and cytochrome P450 (CYP450) polymorphisms on voriconazole (VRC) plasma through concentrations (Cmin) and provide reliable and direct basis for clinical application of VRC. Methods: A total of 918 VRC Cmin from 231 patients was collected and analyzed in this study. VRC Cmin was quantified using high‐performance liquid chromatography. The genotypes of CYP2C19, CYP3A4 and CYP3A5 were detected by DNA sequencing assay. The influences of glucocorticoids co-administration on VRC Cmin were analyzed, and the interactive effects of glucocorticoids with CYP450s on VRC Cmin were also analyzed. Results: The median Cmin of oral administration was lower compared to those of intravenous administration (1.51 vs. 4.0 mg•L-1.). Glucocorticoids (including dexamethasone, prednisone, prednisolone and methylprednisolone) can reduce the VRC Cmin/dose significantly. Compared with co-administration with prednisolone or methylprednisolone, dexamethasone make the median of VRC Cmin/dose ratio more lower. As a result, glucocorticoids increased the proportion of VRC Cmin/dose in the sub-therapeutic window. Mutation of CYP2C19*2, *3 increased Cmin/dose of VRC, while CYP2C19*17, CYP3A4 rs4646437 polymorphism decreased Cmin/dose of VRC. The mutation of CYP3A5 has no significant effect. Among all the mutations, only CYP2C19*17 mutants could strengthen the reduction of glucocorticoids on VRC Cmin/dose. Conclusion: Our study revealed that glucocorticoids reduced the Cmin/dose levels of VRC, and different SNP polymorphisms of CYPs have different effects on the Cmin/dose ratio of VRC. Glucocorticoids and CYP2C19*17 mutate had a synergistic effect on reducing VRC Cmin/dose. The present results suggested that when VRC combined with glucocorticoids, we should pay more attention to clinical efficacy of VRC when CYP2C19*17 mutants exist.